The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1002/jmri.21467
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion‐weighted imaging of the liver: Optimizing b value for the detection and characterization of benign and malignant hepatic lesions

Abstract: Purpose:To determine the optimal b values required for diffusion-weighted (DW) imaging of the liver in the detection and characterization of benign and malignant hepatic lesions. Materials and Methods:MR images obtained in 76 patients including 28 malignant hepatic lesions (21 hepatocellular carcinomas and 7 metastases) and 27 benign lesions (12 hemangiomas and 15 cysts) were reviewed. DWecho planner images (EPIs; b values with100, 200, 400, and 800 s/mm 2 ) were reviewed solely first, and then with T2-weighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 13 publications
7
63
0
2
Order By: Relevance
“…Mean ADC values of cyst and haemangioma were significantly higher than other benign hepatic focal lesions. This coincides with other studies [18] [20] [24].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Mean ADC values of cyst and haemangioma were significantly higher than other benign hepatic focal lesions. This coincides with other studies [18] [20] [24].…”
Section: Discussionsupporting
confidence: 94%
“…[21]. But, it does not correlate with other studies [22]- [24]. The difference may be due to using different b value, different technique either breath-hold or respiratory triggered, or different pathological types of haemangiomas.…”
Section: Discussionmentioning
confidence: 73%
“…DWI is able to differentiate between benign and malignant focal hepatic lesions, in many cases because of the higher ADC of benign lesions compared with malignant lesions (56)(57)(58). This finding is thought to be the result of cellular membranes impeding the mobility of water molecules.…”
Section: Abdominal Applicationsmentioning
confidence: 99%
“…21 Similarly, ADC can be used to separate malignant and benign hepatic lesions. 22 In addition, diffusion MRI has shown great potential for separating benign from malignant head and neck tumors and thereby guiding biopsing. 23 Recent technical advancements in body MR have indicated that DWI may provide valuable information for lymph node staging, 24 which has recently been possible in situ only by radionucleotide techniques, such as PET.…”
Section: Diffusion Mr For Cancer Imaging: Improved Treatment Monitoringmentioning
confidence: 99%